1999
DOI: 10.1038/sj.bjc.6690416
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for characteristic vascular patterns in solid tumours: quantitative studies using corrosion casts

Abstract: The vascular system plays a role of key importance during tumour growth and metastasis formation. In addition, the effectiveness of almost all therapeutic modalities, including drug therapy and radiotherapy, is influenced by the micro-architecture and the gradients of essential nutrients around each vessel. This underlines the importance of the vascular architecture, its origin and effectiveness as a nutrient delivery system. The knowledge that tumour vasculature is abnormal has led to concepts such as angioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
146
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(158 citation statements)
references
References 15 publications
7
146
0
4
Order By: Relevance
“…Earlier corrosion casting works have shown that branching angles and interbranching distances are specific and characteristic for each tissue including tumours (Konerding et al, , 1999. In our case, the vascular branching and bifurcation capillary pattern of the normal testis totally disappeared and the examined specimens exhibited features similar to an immature vascular network with heterogeneous vessel densities, frequent blindending, resin extravasations and vascular compressions (Jain, Angiogenesis of an experimental teratocarcinoma U SilvĂĄn et al 1988).…”
Section: Discussionmentioning
confidence: 71%
“…Earlier corrosion casting works have shown that branching angles and interbranching distances are specific and characteristic for each tissue including tumours (Konerding et al, , 1999. In our case, the vascular branching and bifurcation capillary pattern of the normal testis totally disappeared and the examined specimens exhibited features similar to an immature vascular network with heterogeneous vessel densities, frequent blindending, resin extravasations and vascular compressions (Jain, Angiogenesis of an experimental teratocarcinoma U SilvĂĄn et al 1988).…”
Section: Discussionmentioning
confidence: 71%
“…Using this method we have recently demonstrated tumour typespecific vascular architectures in xenografted murine and human tumours (Konerding et al, 1999). Furthermore, the vascular architecture of an experimental tumour does not depend on the size and/or the rate of growth of the lesion but rather on features characteristic of the tumour cell type.…”
Section: Discussionmentioning
confidence: 96%
“…The casting specimens were prepared for scanning electron microscopy as described in detail earlier (Konerding et al, 1999). From all specimens between 10 and 25 stereo pairs of peripheral and central areas were recorded as stereo images using a tilt angle of 6˚.…”
Section: Microvascular Corrosion Castingmentioning
confidence: 99%
See 1 more Smart Citation
“…These features contribute to a high intrinsic vascular permeability of macromolecules into the vasculature (Dvorak, 1991;Jain, 1987) and the consequent development of high interstitial fluid pressure (Boucher, 1990), which is augmented by inadequate lymphatic drainage. Tumour vascular networks are chaotic, featuring complex branching patterns and lack of hierarchy (Gillies, 1999;Konerding, 1999;Less, 1991). Vessel diameters are irregular and lengths between branching points are often very long.…”
Section: Tumour Vasculature and Antivascular Therapiesmentioning
confidence: 99%